HUBUNGAN GAYA KEPEMIMPINAN DENGAN STRES KERJA PADA GURU DI SMK XYZ PADANG TAHUN 2022 - Aulia, Astrina; Muslim, Fluorina Oryza; Jihan Faradisha,; Jayati, Trisna (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
Introduction :Psychosisal hazards as work stress are an important concern at this time, not least in the work sector such as teachers who tend to experience work stress from various factors. The role of the leader can be a risk factor or vice versa as a protective factor against mental health problems. The purpose study was to examine the relationship between leadership style and job stress on teachers at SMK XYZ Padang. Methods: This study used a cross sectional study design to relate the independent variables and the dependent variable. The population and samples used were 62 teachers. Results: The results are that there is a significant relationship between marital status and work stress (p value = 0.039) and leadership style and work stress (p value = 0.049). Single teachers have a smaller risk of experiencing work stress because life problems are not as complicated as those who are married, while democratic and delegative leadership styles can be a protective factor against the risk of work stress because of the support and direction from the leadership. Conclusion: The role of the leader in the organization is very large and the adjustment of leadership style must be seen from the characteristics of the employees.